Evaluation Of Complete Blood Count Parameters To Predict Ovarian Torsion In Women With Adnexal Mass - Tayyar, Ahter T.; Özkaya, Enis; Yayla, Çiğdem Abide; Şentürk, Mehmet Baki; Selçuk, Selçuk; Polat, Mesut; Cündübey, Cevat Rıfat; Tayyar, Mehmet (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: The aim of this study was to evaluate complete blood count parameters to predict ovarian torsion in cases presented with ovarian mass. Study Design: Pre-operative demographic data and complete blood count parameters of 72 patients, who were operated on preliminary adnexal torsion and diagnosed as adnexal torsion with a benign ovarian cyst (Study group) were retrospectively compared with those of 77 patients who were operated with an indication of persistent benign ovarian cysts without torsion (control group) at Zeynep Kamil Women and Children’s Health Training and Research Hospital and Department of Obstetrics & Gynecology at Erciyes University Medical Faculty between 2011 and 2015. Complete blood count parameters were utilized to predict ovarian torsion cases. Result: Neutrophil (AUC=792, P=<0.001), white blood cell (AUC=787, P=<0.001) counts and neutrophil/lymphocyte ratio (AUC=770, P=<0.001) were significant predictors for adnexal torsion. Optimal cut off value for white blood cell, neutrophil count and neutrophil/lymphocyte ratio were 8.3x103 (72% sensitivity, 73% specificity), 5.5x103 (73% sensitivity, 76% specificity), 2.9 (73% sensitivity, 79% specificity) respectively. Conclusion: Among all the parameters white blood cell count, neutrophil/lymphocyte and neutrophil count were the most powerful predictors for real adnexal torsion cases. Simple blood count parameters detailed evaluation may help clinicians to confirm or rule out adnexal torsion in cases presented with ovarian cyst and adnexal mass.